2010
DOI: 10.1016/j.surg.2010.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia modulates plasminogen activator inhibitor-1 expression and aortic diameter in experimental aortic aneurysm disease

Abstract: Background-Extracellular matrix degradation is a sentinel pathologic feature of abdominal aortic aneurysm (AAA) disease. Diabetes mellitus, a negative risk factor for AAA, may impair aneurysm progression through its influence on the fibrinolytic system. We hypothesize that hyperglycemia limits AAA progression through effects on endogenous plasminogen activator inhibitor-1 (PAI-1) levels and subsequent reductions in plasmin generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 25 publications
4
58
0
Order By: Relevance
“…[27][28][29][30] In addition, ARB and hyperglycemia have inhibited the expansion in animal studies. [31][32][33][34] In the present study, ARB (P=0.025 on univariate analysis) and hyperglycemia (P=0.037 on univariate analysis, P=0.067 on multivariate analysis) tended to be negatively associated with AAA expansion, consistent with previous reports. 31 -34 In addition, we did not observe any suppressive effects on AAA expansion of decreased cholesterol, oral statin use, or lower blood pressure.…”
Section: Other Factorssupporting
confidence: 92%
“…[27][28][29][30] In addition, ARB and hyperglycemia have inhibited the expansion in animal studies. [31][32][33][34] In the present study, ARB (P=0.025 on univariate analysis) and hyperglycemia (P=0.037 on univariate analysis, P=0.067 on multivariate analysis) tended to be negatively associated with AAA expansion, consistent with previous reports. 31 -34 In addition, we did not observe any suppressive effects on AAA expansion of decreased cholesterol, oral statin use, or lower blood pressure.…”
Section: Other Factorssupporting
confidence: 92%
“…The PAI-1 immunostaining was located in the intima and media of the vessel wall. In a rodent model of AAA formation, diabetic mice had decreased aortic diameter, increased plasma PAI-1 levels, and decreased plasmin levels compared with nondiabetic animals undergoing the same procedure (8). Immunostaining confirmed increased intensity of PAI-1 in the diabetic mice, again concentrated in the intima and media of the aorta.…”
Section: Discussionmentioning
confidence: 81%
“…By intracoronary ultrasound, researchers found that diabetics with atherosclerosis have less compensatory coronary artery enlargement than non-diabetics and the researchers considered it can explain the diffuse and accelerated course of coronary artery disease in these patients (38). Patients with a longer duration of diabetes who were treated with insulin had (paradoxically) less reference segment and stenosis plaque accumulation and hyperglycemia increases plasminogen activator inhibitor 1 expression and attenuates AAA diameter had been demonstrated by animal experimental studies (39,40), lowering of serum glucose levels with insulin treatment diminishes this protective effect (41). Other researchers argued that diabetes promotes negative arterial wall remodeling or at least impairs compensatory arterial enlargement during the course of the atherosclerotic process (10).…”
Section: Discussionmentioning
confidence: 99%